Do IMF and World Bank programs induce government crises? An empirical analysis - Axel Dreher; Martin Gassebner (ETH Zurich, KOF Swiss Economic Institute, 2008)
We examine whether and under which circumstances World Bank projects and IMF programs affect the likelihood of major government crises. Using a sample of more than 90 developing countries over the period 1970-2002, we find that crises are on average more likely as a consequence of Bank and Fund involvement. While the effects of the IMF to some extent depend on the model specification, those of the World Bank are shown to be robust to the choice of control variables and method of estimation. We also find that governments face an increasing risk to enter a crisis when they remain under an arrangement once the economy performs better. The (economic) conditions present when a new arrangement is initiated, however, do not affect the impact of Fund and Bank on the probability of a crisis. Finally, while crisis probability rises when a government turns to the IFIs itself, programs inherited by preceding governments do not affect the probability of a crisis.
Keywords: D72; F34; P48; 330; Political Crisis; International Financial Institutions; Politische Stabilität; Anpassungsprogramm des IWF; Entwicklungshilfe; Entwicklungsländer; Welt